Family Vulnerability: Examining The Contributions of Spirituality and Social Support - Islamia, Intan; Arif, Andry Rahman (ANFUSINA: Journal of Psychology, 2025)
Family vulnerability encompasses multiple dimensions, including physical-economic, social, and psychological factors. This study explored the role of spirituality and social support in mitigating family vulnerability. A sample of 189 families was selected using simple random sampling. Data on family vulnerability and social support were collected using questionnaires designed by Sunarti (2021), while spirituality was measured using the DSES questionnaire by Underwood (2020). Data analysis using SPSS revealed significant negative correlations between both spirituality and family vulnerability, as well as social support and family vulnerability. These findings indicate that increased levels of spirituality and social support can serve as protective factors against family vulnerability. Furthermore, subsequent analysis demonstrated that spirituality exerted a stronger influence than social support in reducing specific dimensions of family vulnerability, such as psychological distress. Keywords: Family vulnerability, family resilience, spirituality, social support, family sciences.